Integrated process for high conversion and high yield protein PEGylation. Issue 8 (6th March 2016) - Pfister, David; Morbidelli, Massimo
ABSTRACT: Over the past decades, PEGylation has become a powerful technique to increase the in vivo circulation half‐life of therapeutic proteins while maintaining their activity. The development of new therapeutic proteins is likely to require further improvement of the PEGylation methods to reach even better selectivity and yield for reduced costs. The intensification of the PEGylation process was investigated through the integration of a chromatographic step in order to increase yield and conversion for the production of mono‐PEGylated protein. Lysozyme was used as a model protein to demonstrate the feasibility of such approach. In the integrated reaction/separation process, chromatography was used as fractionation technique in order to isolate and recycle the unreacted protein from the PEGylated products. This allows operating the reactor with short reaction times so as to minimize the production of multi‐PEGylated proteins (i.e., conjugated to more than one polymer). That is, the reaction is stopped before the desired product (i.e., the mono‐PEGylated protein) can further react, thus leading to limited conversion but high yield. The recycling of the unreacted protein was then considered to drive the protein overall conversion to completion. This approach has great potential to improve processes whose yield is limited by the further reaction of the product leading to undesirable by‐products. Biotechnol. Bioeng. 2016;113: 1711–1718. © 2016 Wiley Periodicals, Inc. Abstract : The intensification of the protein PEGylation process is investigated in this work. In order to increase the conversion of the protein, the integration of the chromatographic separation unit with the PEGylation reactor and the recycling of the unreacted protein are implemented. This cyclic process is shown to deliver a higher yield and a better selectivity for the production of mono‐PEGylated protein.